Struktur Komunitas dan Asosiasi Crinoidea (Echinodermata) dengan Bentuk Kehidupan Terumbu Karang di Lereng Terumbu Pulau Pramuka, Kepulauan Seribu - Muhammad Emir Rasyid; Mufti Patria (Innovation Centre for Tropical Sciences, 2025)
Class Crinoidea, or sea lilies, are primitive members of the Echinoderm phylum, playing a crucial ecological role as filter feeders and indicating ecosystem health. Pramuka Island is the administrative center of the Seribu Islands Regency, DKI Jakarta, which is experiencing rapid development and becoming a promising tourism site. These anthropogenic activities may influence the survival of the coral reef ecosystem below the island. Thus, further research on crinoid communities and their relationship with coral reef lifeforms is needed to assess the health of the reef ecosystem amidst increasing anthropogenic activities. The research was done using the belt transect method covering an area of 50×5 m at a depth of 10 m at four research stations, calculating the diversity index, evenness index, dominance index, and density. The association of Crinoidea with coral reef lifeforms was analyzed using the chi-square test. The result showed poor value with an average low diversity index, moderate evenness index, and high dominance index. Capillaster sentosus, the most abundant species at every station, indicates habitat suitability rather than ecological disturbance, and serves as a potential bioindicator for Pramuka Island’s reef health, though its dominance might signal a decline in other species due to competition. There were six pairs of Crinoidea–substrates found to be positively associated, and four pairs of Crinoidea–substrates that were negatively associated. The associations between crinoids and coral reefs, influenced by crinoid morphology, reef stability, and current flow, highlight the need for conservation efforts to preserve these crucial relationships for biodiversity. Keywords: association, community structure, coral reef, crinoids, Pramuka island